Challenges in Quantifying Air‐Water Carbon Dioxide Flux Using Estuarine Water Quality Data: Case Study for Chesapeake Bay. Issue 7 (9th July 2020) - Herrmann, Maria; Najjar, Raymond G.; Da, Fei; Friedman, Jaclyn R.; Friedrichs, Marjorie A. M.; Goldberger, Sreece; Menendez, Alana; Shadwick, Elizabeth H.; Stets, Edward G.; St‐Laurent, Pierre
Abstract: Estuaries play an uncertain but potentially important role in the global carbon cycle via CO2 outgassing. The uncertainty mainly stems from the paucity of studies that document the full spatial and temporal variability of estuarine surface water partial pressure of carbon dioxide ( p CO2 ). Here, we explore the potential of utilizing the abundance of pH data from historical water quality monitoring programs to fill the data void via a case study of the mainstem Chesapeake Bay (eastern United States). We calculate p CO2 and the air‐water CO2 flux at monthly resolution from 1998 to 2018 from tidal fresh to polyhaline waters, paying special attention to the error estimation. The biggest error is due to the pH measurement error, and errors due to the gas transfer velocity, temporal sampling, the alkalinity mixing model, and the organic alkalinity estimation are 72%, 27%, 15%, and 5%, respectively, of the error due to pH. Seasonal, interannual, and spatial variability in the air‐water flux and surface p CO2 is high, and a correlation analysis with oxygen reveals that this variability is driven largely by biological processes. Averaged over 1998–2018, the mainstem bay is a weak net source of CO2 to the atmosphere of 1.2 (1.1, 1.4) mol m −2 yr −1 (best estimate and 95% confidence interval). Our findings suggest that the abundance of historical pH measurements in estuaries around the globe should be mined in order to constrain the large spatial and temporal variability of the CO2 exchange between estuaries and the atmosphere. Plain Language Summary: Carbon dioxide (CO2 ), an important greenhouse gas, is transferred from most estuaries to the atmosphere at a poorly known but potentially large rate. The difficulty in accurately quantifying the transfer is the lack of data of the amount of CO2 in estuarine surface waters. We evaluated the proposition that the abundance of historical water quality measurements of pH could be used to fill this data gap by conducting an analysis of CO2 and its transfer to the atmosphere in surface waters of the mainstem of the Chesapeake Bay, a large estuary of eastern United States. The analysis is unusual because of the large number of observations over many years that were used to calculate the CO2 concentration in estuarine surface waters. CO2 was found to vary greatly throughout the estuary, from season to season, and from year to year. Using measurements of temperature, salinity, and oxygen, we determined that photosynthesis and respiration had a large influence on surface water CO2 . Averaged over 1998–2018, the mainstem of the bay released CO2 to the atmosphere. Our analysis suggests that the approach of using historical water quality measurements should be applied elsewhere to more accurately determine how much CO2 is exchanged between world estuaries and the atmosphere. Key Points: The largest source of error in computing the air‐water CO2 flux from historical Chesapeake Bay water quality data is the measurement of pH Biological processes are a major cause of the spatial and temporal variability in surface water p CO2 in the mainstem Chesapeake Bay Averaged over 1998 to 2018, the mainstem bay was a weak net source of CO2 to the atmosphere of 1.1–1.4 mol m −2 yr −1 (95% confidence range)